If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -3y) * dx + (8x + -3y) * dy = 0 Reorder the terms for easier multiplication: dx(5x + -3y) + (8x + -3y) * dy = 0 (5x * dx + -3y * dx) + (8x + -3y) * dy = 0 Reorder the terms: (-3dxy + 5dx2) + (8x + -3y) * dy = 0 (-3dxy + 5dx2) + (8x + -3y) * dy = 0 Reorder the terms for easier multiplication: -3dxy + 5dx2 + dy(8x + -3y) = 0 -3dxy + 5dx2 + (8x * dy + -3y * dy) = 0 -3dxy + 5dx2 + (8dxy + -3dy2) = 0 Reorder the terms: -3dxy + 8dxy + 5dx2 + -3dy2 = 0 Combine like terms: -3dxy + 8dxy = 5dxy 5dxy + 5dx2 + -3dy2 = 0 Solving 5dxy + 5dx2 + -3dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(5xy + 5x2 + -3y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(5xy + 5x2 + -3y2)' equal to zero and attempt to solve: Simplifying 5xy + 5x2 + -3y2 = 0 Solving 5xy + 5x2 + -3y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-5xy' to each side of the equation. 5xy + 5x2 + -5xy + -3y2 = 0 + -5xy Reorder the terms: 5xy + -5xy + 5x2 + -3y2 = 0 + -5xy Combine like terms: 5xy + -5xy = 0 0 + 5x2 + -3y2 = 0 + -5xy 5x2 + -3y2 = 0 + -5xy Remove the zero: 5x2 + -3y2 = -5xy Add '-5x2' to each side of the equation. 5x2 + -5x2 + -3y2 = -5xy + -5x2 Combine like terms: 5x2 + -5x2 = 0 0 + -3y2 = -5xy + -5x2 -3y2 = -5xy + -5x2 Add '3y2' to each side of the equation. -3y2 + 3y2 = -5xy + -5x2 + 3y2 Combine like terms: -3y2 + 3y2 = 0 0 = -5xy + -5x2 + 3y2 Simplifying 0 = -5xy + -5x2 + 3y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| x^2-3x-1=-2 | | -17+x-5=-15+1 | | 6r-8=2r-4 | | 8x+10=x+45 | | 108+6x=189 | | (x-5)-(x-1)=4 | | 5y-5=y+15 | | -9h-(2+5h)+3h-7= | | 17-8+x=8+5-3 | | 4w+3=-7w+36 | | 7+1+x=5+3 | | 5x^2+9x+10=0 | | 25=3(2h-2)+7 | | x^2+2x-4=-8 | | 34-19=x-7 | | 2(3a+7)=14 | | 18x=7x+33 | | (3x^7+6x^4-5x+7)-(6x^4-5x^3+7)= | | x^2+4x+8=32 | | 18=6-3y | | 0.5(m+9)=6 | | 3x+9=-(x+7) | | 2=u-8 | | -4*4=-4y | | 2(3x-6)=(3x-14) | | 64/(15-7)(2)-9 | | H+9=9 | | 3x+18=x-8 | | 5+(-2)-7-4+3= | | 63+2x+9=180 | | (6x^7-x+8)-(x^7+2)= | | -5x^2-18x+79=0 |